Penguatan Kompetensi Sumber Daya Manusia dalam Optimalisasi Media Sosial sebagai Strategi Branding dan Promosi Digital pada Maka Coffe Makassar - Andi Indra Saputra Alamsyah; Kurniati Asmar; Tri Wahyu Septyani; Risnawati Risnawati; Maududi Lamparawi Magenda (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Strengthening human resource (HR) capacity in digital marketing is essential for micro, small, and medium enterprises (MSMEs) in responding to digital transformation. Maka Coffee faces challenges in managing social media, including inconsistent content creation, limited use of analytics, and suboptimal digital branding. This community service program aims to enhance HR competencies through training, mentoring, and simulation. The program was implemented in four stages: preparation (observation and analysis), practice-based training, mentoring, and social media simulation. Evaluation used pre-test and post-test methods across five indicators: digital branding, social media management, content creation, use of digital tools (Canva), and engagement and analytics. The results show a significant improvement in participants’ competencies, with an average increase of more than 40%. The highest improvement occurred in content creation (45.16%). These findings indicate that practice-based training and mentoring effectively improve MSMEs’ digital marketing skills in a structured and practical manner.